2005
DOI: 10.1079/phn2005747
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the nutrition transition in two Mediterranean islands: Sardinia and Malta

Abstract: Objective: To examine and analyse consumption changes over time of 24 food items between Sardinia and Malta. Setting: The data were collected in 2001 in Sardinia and 2002 in Malta. Design: A structured qualitative questionnaire, articulated around four main themes: food supply, transformation, preparation and consumption habits, was administered by face-to-face interviews with the help of a local person.It encompassed mainly open-ended questions, which allowed us to measure factors contributing to change. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 8 publications
5
60
2
2
Order By: Relevance
“…compared to 2154levels in Sardinia) have played a role. This relationship has been mediated both via the introduction of new foods and by the demands of the tourism industry on domestic production (52,53) . As an outcome of reducing restrictions on foreign ownership of companies, the developing world has also seen an increase in investment by advertising corporations.…”
Section: Investment and Trade In Servicesmentioning
confidence: 99%
“…compared to 2154levels in Sardinia) have played a role. This relationship has been mediated both via the introduction of new foods and by the demands of the tourism industry on domestic production (52,53) . As an outcome of reducing restrictions on foreign ownership of companies, the developing world has also seen an increase in investment by advertising corporations.…”
Section: Investment and Trade In Servicesmentioning
confidence: 99%
“…Seven pan-European studies (44,46,68,81,83,92,94) used diet records or diaries, either a 7 d record or three consecutive day records. With the exception of studies which used weighed records (83) or a mixed approach (81) , most studies estimated portion size using photographs (30,46,91) , household measures and objects (e.g.…”
Section: Diet Records/diet Diariesmentioning
confidence: 99%
“…From the sourced articles, fifty-one pan-European studies in total were identified: thirty-five named projects and sixteen smaller projects (48,54,56,65,69,72,82,83,88,93,94,107,109,113,114,116) . Most studies assessed dietary intake of F&V among adults (18,41,44,46,48,50,51,(54)(55)(56)(57)59,60,(64)(65)(66)68,69,71,72,(75)(76)(77)(78)(79)(81)(82)(83)(84)86,88,(92)(93)(94)107,…”
Section: Public Health Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the historical influences outlined above, systematic changes to global food production and distribution systems, improving economic conditions and a dependence on foreign imports have consolidated the shift away from the traditional Mediterranean diet (46,47) and led to the adoption of a more 'Westernised' diet high in refined carbohydrates, meat, SFA and salt (34,35,48) . Thus, a century-and-a-half later, a 1986 WHO report portrayed the Maltese diet as an unhealthy one rich in fats and sugar and low in fibre, designating the Maltese as a high-risk group for non-communicable disease (49) .…”
Section: Colonial Impactmentioning
confidence: 99%